Electro-fermentative production of thermotolerant lipases by electrogenic bacteria isolated from palm oil mill effluents - E.O. Garuba; O.M. Ajunwa; O.S. Oguntomi; A.A. Onilude (Novel Research in Microbiology Journal)
This study aimed at assessing the effects of Bio-electrochemical system on the yield of thermostable lipase produced by Bacillus licheniformis S1S2, Bacillus pulmilus S1E23, Bacillus sp. S1E27, and Aeribacillus sp. S1E29. With physiological conditioning of the lipolytic activities, comparative production of thermostable lipase by the selected isolates was carried using submerged fermentation and electro-fermentation methods. An optimum lipase yield of 95.1± 0.003 U/ ml, 128± 0.001 U/ml, 110.7± 0.003 U/ ml and 122.7± 0.002 U/ml was produced by B. licheniformis S1S2, B. pulmilus S1E23, Bacillus sp. S1E27, and Aeribacillus sp. S1E29; respectively, under conventional fermentation process. However, under electro-fermentation, increased enzyme yields of 129.6± 0.002 U/ml, 164.9± 0.001 U/ml, 125.3± 0.002 U/ml, and 136.6± 0.001 U/ml, for same respective isolates was obtained. The biophysical characteristics of the enzymes produced showed that the thermostable lipases had optimum activity at a temperature range of 45oC - 55oC, pH of 7 - 9, and enhanced activity in the presence of Ca2+, Mg2+, and Zn2+, however, Hg2+ caused a slight loss in the lipase activity.